Prolog to the Section on Wireless Communications Technology - Hanzo, L; Haas, H; Imre, S; O'Brien, D; Rupp, M; Gyongyosi, L (2012)
A special Issue of the Proceedings of the IEEE takes a closer look at the existing third-generation (3G) systems in service and investigated their capabilities with the aid of measurements. The associated performance losses into a few subclasses are categorized. The availability of accurate channel state information (CSI) at the transmitter may be expected to considerably improve the achievable throughput of the system, while its inaccurate knowledge would naturally erode the maximum attainable performance. Studied have also shown that cellular standards are based on a carefully negotiated compromise, which might influence the direction of technological advances. It is also found that the promising link level gains are often eroded in a multicell system deployment, especially in the absence of advanced techniques such as intelligent and practically realizable interference management. Some recent results in the area of visible light communication are also presented.